2015
DOI: 10.1111/gcb.13028
|View full text |Cite
|
Sign up to set email alerts
|

Net effects of multiple stressors in freshwater ecosystems: a meta‐analysis

Abstract: The accelerating rate of global change has focused attention on the cumulative impacts of novel and extreme environmental changes (i.e., stressors), especially in marine ecosystems. As integrators of local catchment and regional processes, freshwater ecosystems are also ranked highly sensitive to the net effects of multiple stressors, yet there has not been a large-scale quantitative synthesis. We analysed data from 88 papers including 286 responses of freshwater ecosystems to paired stressors, and discovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
700
10
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 691 publications
(746 citation statements)
references
References 66 publications
34
700
10
2
Order By: Relevance
“…The identity of dominant drivers in each regime partially explains the small differences in the response to selection in multidriver environments. The overriding effect of the dominant drivers is consistent with the acclimation response to these regimes (7), scenario-based experiments (8), and many physiological responses of microalgae to pairs of drivers (31)(32)(33)(34)(35). Our data are consistent with either small effects of driver interactions relative to the effects of dominant drivers or (nearly) zero-sum interactions among drivers.…”
Section: Discussionsupporting
confidence: 82%
“…The identity of dominant drivers in each regime partially explains the small differences in the response to selection in multidriver environments. The overriding effect of the dominant drivers is consistent with the acclimation response to these regimes (7), scenario-based experiments (8), and many physiological responses of microalgae to pairs of drivers (31)(32)(33)(34)(35). Our data are consistent with either small effects of driver interactions relative to the effects of dominant drivers or (nearly) zero-sum interactions among drivers.…”
Section: Discussionsupporting
confidence: 82%
“…However, substantial unexplained variation indicates that further comparative research is required to develop a comprehensive picture of litter breakdown in streams at the global scale. Such understanding is vital to appropriate management of these ecosystems in the face of multiple anthropogenic stressors [72,73]. …”
Section: Resultsmentioning
confidence: 99%
“…Except for the internal zinc concentrations, which were log‐transformed, the assumptions of ANOVA (normally distributed errors and homogeneity of variances) were met for all variables. When an interaction effect between temperature and the nZnO treatment was detected, the type of interaction was identified by calculating the interaction effect size (estimated as Hedges'd with 95% confidence interval) (Jackson et al., 2016). An interaction effect size larger than zero indicates a synergistic interaction among stressors, while an interaction effect size smaller than zero indicates an antagonistic or reversal interaction.…”
Section: Methodsmentioning
confidence: 99%
“…80% of the studies showed a synergistic interaction between a contaminant and heat stress for traits such as survival, developmental rate, and hatching success. Jackson, Loewen, Vinebrooke, and Chimimba (2016) showed that ca. 30% of the studies testing combined effects of warming and contaminants in freshwater ecosystems showed a synergism for traits such as growth and reproduction.…”
Section: Introductionmentioning
confidence: 99%